(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
God – The Basis and the Fulfilment of Human Dignity Human dignity is fulfilled in achieving its purpose—being in communion with God and with the whole creation, the work of God. Thus, as the last creation of God, the basis and the fulfilment of human dignity is its Creator himself, the one who made us “in his image”, with the purpose of being changed “into his likeness”. He gave us many gifts, including the freedom of becoming what we freely choose to become. Human dignity implies the fulfilment of the call to the perfection of the human being, but also of the kingdom over which we were named while being filled with the grace of God. Any attempt to carve human dignities based on certain particular premises—reduction to material, reduction to the fulfilment of selfish lust, the depersonalisation of the individual, etc.—without taking into account the dichotomous structure of the human being—soul and body—shall lead to dehumanization. From these perspectives and many others, human dignity is fulfilled through the free and conscious communion with the Creator and with the whole creation.